Upaya Peningkatan Perilaku Pencegahan DBD Melalui Program Pemberdayaan Masyarakat - Aldi Syahputra Nasution; Azzahra Ramadhana Nasution; Dwika Ardelya Pratiwi; Novi Andaresta; Salshabila Azzahra Sirait; Tiara Pakar Ningrum; Yendika Mailina br Ginting; Nisrina (PT. Alahyan Publisher Sukabumi, 2023)
Dengue hemorrhagic fever or DHF is a disease spread through mosquitoes, often occurring in tropical and subtropical areas throughout the world. The common symptoms of dengue hemorrhagic fever (DHF) are high fever and other flu-like symptoms. One of the four types of dengue virus is the cause of dengue fever. We can get infected not because we are around people who are infected, but because this disease is transmitted through mosquito bites. Two mosquitoes that can transmit this virus are Aedes aegypti and Aedes albopictus. These two types of mosquitoes are often found around residential areas. Until now, dengue hemorrhagic fever (DHF) is still a problem in society. This research aims to find new forms of efforts or ideas related to community empowerment in efforts to prevent and control the incidence of dengue hemorrhagic fever (DHF). This research uses a literature study that examines various references that are closely related to dengue fever, with Google Scholar as a source for searching for articles that the author uses in this research. The articles that the author uses are articles from at least 2018, both articles and journals. We used 10 journals identified from Google Scholar. This literature review can provide recommendations regarding the role of the community in improving the implementation of every dengue control program in Indonesia.